TYPES OF GRAMMATICAL ERRORS IN THE ESSAYS WRITTEN BY FOURTH-SEMESTER STUDENTS OF ENGLISH DEPARTMENT, PETRA CHRISTIAN UNIVERSITY - D. Handayani; Flora Debora Floris (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This study observed the apology strategies used by five customer service officers of Mandiri Bank and five customer service officers of Mega Bank in Surabaya. The data were analyzed using the theory of apology strategies proposed by Trosborg (1995). The findings show that both the customer service officers of Mandiri and Mega Bank mostly used Checking strategy when handling the complaints. Overall, it was found that all customer service officers used seven types of apology strategies and they did not use sixteen apology strategies. This happened probably probably because they had tendency to use strategies commonly used among Indonesians and probably because they were not trained to use other strategies.